Avaliação da centralização do preparo do canal radicular e da fadiga do instrumento comparando três sistemas rotatórios de níquel-titânio - Bürgel, Marília Ostermann (2012)
Introduction: This in vitro study evaluated the capacity of centralization of the preparation, as well as the wear, distortion and fracture of three rotary nickel-titanium (Ni-Ti) systems Wizard CD Plus (WP), Wizard Navigator (WN) and BioRace(BR). Methodology: Were used 90 mesiobuccal roots (MV) of first upper molars (MS). The overlap of tomographic images before and after instrumentation was used to evaluate the transport of the preparation, at 2.0, 4.0, 6.0 and 8.0 mm from the apex. The instruments were observed by SEM before and after the third use, at its tip and at 5 mm of it. The data were analyzed by Kruskal-Wallis, complemented by Tukey test (P<0.05). Results: There was transport of the root canal in all groups, with no statistical difference between them (P> 0.05). There was no fracture and distortion at 5mm from the tip of the instruments. The group BR exhibited more distortion at the tip than the group WP (P = 0.011). There was more wear of the instrument in the group WP than in the BR (P <0.001). There was a progressive increase in distortion at the tip (P = 0.026) and of the wear (P <0.001) compared to the use in the group BR, as well as the wear in the group WP (P<0.001). Conclusion: None of the rotary systems employed was able to provide centralized preparation and the progressive use of the instruments did not favor the occurrence of fracture despite having increased the occurrence of distortion and wear